2015
DOI: 10.1007/s00253-015-6654-6
|View full text |Cite
|
Sign up to set email alerts
|

Plant antifungal proteins and their applications in agriculture

Abstract: Fungi are far more complex organisms than viruses or bacteria and can develop numerous diseases in plants that cause loss of a substantial portion of the crop every year. Plants have developed various mechanisms to defend themselves against these fungi which include the production of low-molecular-weight secondary metabolites and proteins and peptides with antifungal activity. In this review, families of plant antifungal proteins (AFPs) including defensins, lectins, and several others will be summarized. Moreo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
27
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 59 publications
(27 citation statements)
references
References 247 publications
(221 reference statements)
0
27
0
Order By: Relevance
“…Certain plants produce antifungal proteins to defend against fungal growth. 10 Isolating these antifungal proteins and inserting them into different plants increases resistance against fungal pathogens in these new host plants. These proteins include chitinases and glucanases.…”
Section: Introductionmentioning
confidence: 99%
“…Certain plants produce antifungal proteins to defend against fungal growth. 10 Isolating these antifungal proteins and inserting them into different plants increases resistance against fungal pathogens in these new host plants. These proteins include chitinases and glucanases.…”
Section: Introductionmentioning
confidence: 99%
“…and it was found that the purified protein remained thermostable up to 60°C and exerted inhibitory effect on pathogengic fungal growth, but it was rapidly inactivated when incubated at temperature above 60 C. Plants defend themselves against pathogens by producing secondary metabolites and proteins with antifungal activity. Yan . (2015) reviewed plant antifungal proteins and their applications in agriculture emphasizing thermostability and activity over a wide range of pH as desirable traits of such proteins.…”
Section: Isolation Of Proteinmentioning
confidence: 99%
“…Thus, it is of utmost importance to screen for new antifungal substances characterized by safety, high efficiency, environmental friendliness, and lower fungicide resistance. Among the candidates, antifungal peptides have considerable application potential and attracted attention [9,10,11,12].…”
Section: Introductionmentioning
confidence: 99%